The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1152/ajpgi.00077.2004
|View full text |Cite
|
Sign up to set email alerts
|

Muscularis inflammation and the loss of interstitial cells of Cajal in the endothelin ETB receptor null rat

Abstract: Endothelin receptor null rats [ETB(-/-)] are a model for long-segment Hirschsprung's disease. These animals have significant intestinal distension (megaileum) proximal to a constricted region of the gastrointestinal tract lacking enteric ganglia. Experiments were performed to determine the pathophysiological changes that occur in these animals and to examine the tunica muscularis as a unique, immunologically active compartment. We observed abnormal intestinal flora in ETB(-/-) rats, which included a marked inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 31 publications
(32 reference statements)
4
56
1
Order By: Relevance
“…In the murine bone marrow-derived macrophages, phagocytosable size of latex beads (1.1-µm) stimulated the release of PGE 2 , whereas these macrophages did not respond to nonphagocytosable particles (≥ 40-µm) [24]. In the present study, we demonstrated that the injected FITC-dextran was phagocytosed by muscularis resident macrophages in rat small intestine same as previous reports [15,20,26]. The confocal microscopic study for FITC-dextran uptake and immunohistochemical study based on the results of double staining of dextran and COX-2 protein suggest that FITC-dextran-positive resident macrophages became immunoreactive to COX-2 antibody (Figs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the murine bone marrow-derived macrophages, phagocytosable size of latex beads (1.1-µm) stimulated the release of PGE 2 , whereas these macrophages did not respond to nonphagocytosable particles (≥ 40-µm) [24]. In the present study, we demonstrated that the injected FITC-dextran was phagocytosed by muscularis resident macrophages in rat small intestine same as previous reports [15,20,26]. The confocal microscopic study for FITC-dextran uptake and immunohistochemical study based on the results of double staining of dextran and COX-2 protein suggest that FITC-dextran-positive resident macrophages became immunoreactive to COX-2 antibody (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…In the animal models for inflammatory bowel disease (IBD) or Hirschsprung's disease, the inflammation of intestinal muscularis is accompanied with the increase in the number of resident macrophage at the level of myenteric plexus layer [10,26]. In the present results, however, the number of ED2 positive cells was not changed in the dextran injected rat (Fig.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…MEA has also been applied to investigate spontaneous electrical activity between ileal musculature preparations from WT and W/W v mice. This comparison provides a model to evaluate impairment of the ICC network, because it is well known that the latter has a largely reduced population of ICC-MyP due to a partial loss-of-function mutation of Kit receptors (Reith, 1990;Ward et al 2004;Iino et al 2007). Analyses with power spectrum and potential mapping successfully distinguished electrical properties of these musculature preparations, indicating that network-forming ICC-MyP not only generates pacemaker potentials but also co-ordinates basal electrical activities.…”
Section: Applications Of Mea In Gut Pacemakersmentioning
confidence: 99%
“…and W/ W v mice as a model to evaluate the impairment of ICC, because it is well known that the latter has a largely reduced population of ICC in the myenteric region due to partial loss-of-function mutation of Kit receptors (Reith, 1990;Ward et al 2004;Iino et al 2007). Fig.…”
mentioning
confidence: 99%